Africa's return migrants The new developers? - Åkesson, Lisa; Eriksson Baaz, Maria (Africa Now, 2015)
Many African migrants residing abroad nurture a hope to one day return, at least temporarily, to their home country. In the wake of economic crises in the developed world, alongside rapid economic growth in parts of Africa, the impetus to 'return' is likely to increase. Such returnees are often portrayed as agents of development, bringing with them capital, knowledge and skills as well as connections and experience gained abroad. Yet, the reality is altogether more complex. In this much-needed volume, based on extensive original fieldwork, the authors reveal that there is all too often a gaping divide between abstract policy assumptions and migrants' actual practices. In contrast to the prevailing optimism of policies on migration and development, Africa's Return Migrants demonstrates that the capital obtained abroad is not always advantageous and that it can even hamper successful entrepreneurship and other forms of economic, political and social engagement.